Role of Intellectual Property System in Ensuring Access to Books - Onoyeyan, Glory O.; Bamidele, Itunu Adeola (Communicate: Journal of Library and Information Science, 2024)
Access to information is a universal right that is protected by law and to be enjoyed by all. Access to books makes for better people, and for more responsible citizens. Intellectual property seeks to protect the intellectual property of creators and to also ensure that access to information I s not inhibited. Books are a primary source of information and available reference for research in both its traditional and digital formats. With the methodology of simple literature review, the paper made efforts to review the role of intellectual property system in ensuring access to books, while highlighting the provisions of the Nigerian Copyright Act. The intellectual property system and the various copyright exceptions created by the intellectual property system to guarantee access to information are underscored in the paper. The paper therefore highligthed the principles of fair use, library privilege, compulsory licensing, use of a work in an approved educational Institution, etc.,to promote access to books include. The paper also covered the rights of the visually impaired to copyright works, like every other sighted person, as equal access to books and other educational materials presents equal opportunities for all to acquire education, develop skills, and realise their full potential.